Presidential system in crisis? an analysis of governability and political crises - de Carvalho, Eduardo Fortes Portela (Seven Editora, 2023)
The 1988 Federal Constitution defined the presidential as the system of government and implemented a multi-party system. Linz (1990) argues that this combination would generate constant political crises, as it would hinder the formation of legislative majorities and lead to ungovernability. In addition, the constitutional text conferred legislative powers to the president, such as the possibility of issuing provisional measures. Mainwaring (1993) argues that minority presidents could use this power to bypass the legislature and impose their political agenda, leading to instability between the branches. It is undeniable that since the promulgation of CF/88 political crises has been recurrent, including two presidents who had their terms of office prematurely terminated by the Legislative Branch. This study aims to analyze whether the presidential system combined with the multiparty system and the agenda powers attributed to the president are determinants to generate ungovernability and foster institutional crises within the Legislative Branch. DOI: https://doi.org/10.56238/devopinterscie-043